The role of adult attachment and alexithymia in dyadic adjustment - Annunziata Romeo; Agata Benfante; Lorys Castelli; Marialaura Di Tella (Journal of Affective Disorders Reports, 2024)
Background: The present study aimed to investigate if romantic attachment dimensions and alexithymia could significantly predict the dyadic adjustment of individuals in a romantic relationship. Methods: To achieve these goals, 410 participants, who were in a romantic relationship, were asked to complete an anonymous online survey, which included the following measures: Toronto Alexithymia Scale, Experience in Close Relationship Scale and Dyadic Adjustment Scale. Results: The hierarchical regression analysis revealed that only avoidant attachment dimansion was a significant predictor of dyadic adjustment in the final model. However, alexithymia was found to be negatively and indirectly associated with dyadic adjustment through the effect of avoidant attachment. Indeed, avoidant attachment significantly mediated the association between alexithymia and dyadic adjustment. Limitations: We used self-report measures, and we adopted a cross-sectional design. The sample comprised a higher number of women and well-educated participants. Conclusions: The current findings highlight the importance, from a clinical perspective, of paying attention to the planning of tailored psychological treatments directed at individuals who are in a relationship to reduce the levels of insecure attachment and alexithymia.